Microbial Bioerosion of Erratic Sub-Fossil Nautilus Shells in a Karstic Cenote (Lifou, Loyalty Islands, New Caledonia). Issue 1 (2nd January 2016) - Seuss, Barbara; Wisshak, Max; Mapes, Royal H.; Hembree, Daniel I.; Landman, Neil; Lignier, Vincent
Abstract: In a cenote formed in the limestone karst of Lifou (New Caledonia), more than 35 shells of Nautilus macromphalus were discovered in 35–40 m water depth. Seven shells were recovered and subsamples of two shells were used for a study on microbial bioerosion. Both shells were intensively bioeroded and SEM-analyses revealed a total of six ichnotaxa with a dominance of the cyanobacterial trace Scolecia filosa . Such a low diversity ichnocoenosis and the strong dominance of a single ichnotaxon indicate that the environment in the cenote was hostile for many euendolithic organisms. The unfavourable conditions were caused by (1) restricted water-mass exchange with the open ocean, limiting the chance of larvae being transported into the cenote; (2) intense fluctuations in fresh water influx in the karst system promoting traces of euryhaline euendoliths ( Ichnoreticulina elegans, S. filosa, Scolecia serrata ); and (3) very limited light availability, allowing the development of traces of organotrophs ( S. serrata, Flagrichnus profundus ) and the most effective among the photoautotrophs only ( I. elegans, S. serrata, and 'Conchocelis'-stages of bangiacean rhodophytes), indicating deep-euphotic to dysphotic conditions and leading to the observed low ichno-diversity. These results foster the knowledge on the environmental tolerance of microbioerosion trace makers, helping to draw conclusions regarding the characteristics of other extreme (palaeo)environments.